2020
DOI: 10.1016/j.infsof.2019.106225
|View full text |Cite
|
Sign up to set email alerts
|

Management of quality requirements in agile and rapid software development: A systematic mapping study

Abstract: Context: Quality requirements (QRs) describe the desired quality of software, and they play an important role in the success of software projects. In agile software development (ASD), QRs are often ill-defined and not well addressed due to the focus on quickly delivering functionality. Rapid software development (RSD) approaches (e.g., continuous delivery and continuous deployment), which shorten delivery times, are more prone to neglect QRs. Despite the significance of QRs in both ASD and RSD, there is limite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 56 publications
(148 reference statements)
0
78
0
3
Order By: Relevance
“…Regarding their capability for rapid delivery of working software and responding to changing requirements, ASD approaches have been popular and widely adopted in the software industry [29]. Nevertheless, studies reveal that ASD approaches have limitations regarding the specification and documentation of QRs [2,7,9,14,20]. For instance, the capability of ASD user stories to specify and document QRs is limited [7,9,20,22].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding their capability for rapid delivery of working software and responding to changing requirements, ASD approaches have been popular and widely adopted in the software industry [29]. Nevertheless, studies reveal that ASD approaches have limitations regarding the specification and documentation of QRs [2,7,9,14,20]. For instance, the capability of ASD user stories to specify and document QRs is limited [7,9,20,22].…”
Section: Related Workmentioning
confidence: 99%
“…Alsaqaf et al [2] found that ASD teams face trouble in writing Definition of Done (DoD) of QRs and that the lack of understanding of QRs created a challenge for writing the DoDs. Behutiye et al [7], identified that documenting QRs improperly (e.g. unclear specifications, outdated and missing QRs documentation) is one of the challenges of managing QRs in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Functional requirements are usually specified as user stories in a product backlog and prioritized using a customer perspective. This approach tends to naturally favor functional requirements over QRs [10]. As a result, quality aspects such as system security, performance or usability are often compromised [7].…”
Section: Quality Awarenessmentioning
confidence: 99%
“…For example, technical debt (TD) has become a popular concept in Agile software development owing to the specific characteristics of ASD that make it prone to incurring TD [9]. Moreover, in a software development approach driven by functionality, the way in which QRs should be managed is unclear [10]. In this sense, the technical solutions provided by Q-Rapids (the Q-Rapids data gathering and analysis engine -Section 3, and the Q-Rapids dashboard -Section 5) aim to complement Agile and Rapid software development processes by incorporating three key process characteristics: quality awareness, data-driven decision making and rapid (lightweight) development.…”
mentioning
confidence: 99%
“…Together with the fact that an increasing number of companies, regardless of size, are adopting agile methods (Rodriguez et al 2012;VersionOne Inc. 2016), it is important to understand how QRs are or should be managed in ASD. Recent secondary studies on requirements engineering (RE) in ASD have highlighted the importance of QRs and have emphasized that managing QRs in the context of ASD is both challenging and understudied (Schön et al 2017;Heck and Zaidman 2016;Heikkilä et al 2015;Inayat et al 2015;Magües et al 2016;Alsaqaf et al 2017;Behutiye et al 2019). Some of these studies-for example, Inayat et al (2015) and Alsaqaf et al (2017)-also concluded that there is a lack of empirical evidence on how QRs are managed in ASD.…”
Section: Introductionmentioning
confidence: 99%